Clinical significance of lnc-AC145676.2.1-6 and lnc-TGS1-1 and their variants in western Chinese tuberculosis patients. (July 2019) - Bai, Hao; Wu, Qian; Hu, Xuejiao; Wu, Tao; Song, Jiajia; Liu, Tangyuheng; Meng, Zirui; Lv, Mengyuan; Lu, Xiaojun; Chen, Xuerong; Zhou, Yanhong; Ying, Binwu
Highlights: The profiles of laboratory results are presented for a western Chinese population. lnc-AC145676.2.1-6 and lnc-TGS1-1 were down-regulated in TB patients. Down-regulated lnc-TGS1-1 was associated with thrombocytopenia. rs4737420 of lnc-TGS1-1 was correlated with leukopenia. Abstract: Objectives: Tuberculosis (TB) remains a global public health problem. Recent studies have implicated long non-coding RNAs and their variants as possibly playing important roles in TB. The aim of this study was to assess the clinical relevance of lnc-AC145676.2.1-6 and lnc-TGS1-1 and their variants in a western Chinese population. Methods: This case–control study included 467 TB patients and 473 healthy controls from West China Hospital. The expression levels of lnc-AC145676.2.1-6 and lnc-TGS1-1 were analyzed by reverse transcriptase quantitative real-time PCR. Single-nucleotide polymorphism genotyping was performed using a custom-designed 2 × 48-Plex SNPscan kit. Results: It was observed that lnc-AC145676.2.1-6 and lnc-TGS1-1 expression levels were both obviously down-regulated in TB patients. In addition, a lower expression level of lnc-TGS1-1 was associated with the presence of thrombocytopenia in TB patients during anti-TB treatment, and the homozygous CC genotype of rs4737420 correlated with a decreased risk of leukopenia, compared with individuals with the T allele (TT/CT genotype), in the dominant mode. Conclusions: For the first time, potential TB-associated promoting effects were identified for the decreased expression levels of lnc-AC145676.2.1-6 and lnc-TGS-1, while lnc-TGS1-1 and its variant rs4737420 may be predictive indicators of anti-TB drug-induced adverse drug reactions. Larger validation studies on different populations are warranted to confirm these findings.